A Mathematical Study on Non-linear Simultaneous Differential Equations of Blood- Based Casson Nanofluid - Lakshmi, C. Gantha; Ananthaswamy, V.; Sivasankari, S.; Subha, M. (Discontinuity, Nonlinearity, and Complexity, 2026)
A semi-analytical exploration is carried out on the flow of blood-based Casson nanofluid through an elongating sheet having partial slip concerning the implications of thermophoresis and also Brownian motion. The controlling partial differential equations are shifted to ordinary differential equations with the utilization of the similarity transformation. The semi-analytical expressions for non-dimensional velocity, dimensionless concentration, and dimensionless temperature are attained by adopting the Modified Homotopy Analysis technique. Graphical diagrams represent the numerous physical aspects of the system and illustrate their impact. Furthermore, the dimensionless skin friction factor, dimensionless Sherwood number, and non-dimensional Nusselt number are interlined graphically and shown numerically in tables. The error percentage is computed to establish the efficiency and precision of the strategy presented.